1996
DOI: 10.1093/hsw/21.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Online Help: Cancer Patients Participate in a Computer-Mediated Support Group

Abstract: This study investigated a computer mediated support group of six breast cancer patients. For a three-month period, patients used home computers to connect to a computer bulletin board on which they read messages from and posted messages to each other. The patients had no difficulty learning to use the computer and used it an average of one hour a week. The patients discussed their medical conditions, shared personal concerns, and offered support. This online approach provided many features of traditional face-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
0
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(61 citation statements)
references
References 0 publications
2
53
0
2
Order By: Relevance
“…In particular, informational and emotional support were the most frequently provided, and appeared to be linked to the unique challenges faced by individuals who are affected by HD. The prevalence of both these categories of support within the present data is consistent with content analyses of bulletin boards for other chronic conditions [4,33,34]. In addition, it mirrors findings from the literature on face-to-face self-help groups [35].…”
Section: Discussionsupporting
confidence: 88%
“…In particular, informational and emotional support were the most frequently provided, and appeared to be linked to the unique challenges faced by individuals who are affected by HD. The prevalence of both these categories of support within the present data is consistent with content analyses of bulletin boards for other chronic conditions [4,33,34]. In addition, it mirrors findings from the literature on face-to-face self-help groups [35].…”
Section: Discussionsupporting
confidence: 88%
“…Internet-based support groups for both patients and caregivers have also received substantial research attention [e.g., 2,5,19,20]. These online support groups offer participants a place for social support and sharing of knowledge.…”
Section: Motivation and Backgroundmentioning
confidence: 99%
“…27 The few published reports of web-based breast cancer groups have been either in the form of surveys, analysis of participants' communications, 28,29 or uncontrolled studies. 30 Randomized trials are needed to demonstrate the effectiveness of these interventions, particularly regarding their psychologic benefits.…”
mentioning
confidence: 99%
“…Weinberg et al 29 investigated the impact of a computer bulletin board on six women with breast carcinoma. They found that group members actively used the support group to discuss their medical condition, offer support to each other, and to share their personal concerns.…”
mentioning
confidence: 99%